2009
DOI: 10.1097/prs.0b013e3181bceea5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Dissection and Modified Sihler Stain of the Lower Branches of the Facial Nerve

Abstract: A detailed description of the anatomy of the cervical branch is provided. Coinnervation of the lower lip depressors by the cervical branch remains a plausible explanation for the lower lip deformity attributed to cervical branch paralysis in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Secondly malfunction of the lower lip domain caused by the transection of the platysma muscle may at Wrst minimic MMN paresis and last until the muscle had successfully healed and the function restored [2]. Recent studies show evidence of a communication between the marginal mandibular and cervical nerve branches, which also could explain cases of lip depressor deWciency after dissection in level III and IV [23]. Moreover, injury to the thin descending cervical division of the facial nerve as often happens during parotidectomy may also contribute to temporary malfunction of the platysma muscle [2].…”
Section: Discussionmentioning
confidence: 97%
“…Secondly malfunction of the lower lip domain caused by the transection of the platysma muscle may at Wrst minimic MMN paresis and last until the muscle had successfully healed and the function restored [2]. Recent studies show evidence of a communication between the marginal mandibular and cervical nerve branches, which also could explain cases of lip depressor deWciency after dissection in level III and IV [23]. Moreover, injury to the thin descending cervical division of the facial nerve as often happens during parotidectomy may also contribute to temporary malfunction of the platysma muscle [2].…”
Section: Discussionmentioning
confidence: 97%
“…It run downward to get the platysma muscle. It was described as a single branch (15%), a double branch (55%), or having three branches (30%) (Salinas et al, ). We just found one case of a double branch (2.6%) and another one with three branches (2.6%).…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 20 hemifaces, the cervical branch was found to have great variability in terms of number of branches and branching pattern. 37 None of the cervical branches was ever more than 15 mm posterior to the mandibular angle or 45 mm below the inferior mandibular border. Only three of the 20 specimens had a single cervical branch, with two cervical branches being most common (11 of the 20 specimens), followed by three cervical branches in the remaining six specimens.…”
Section: Cervical Branch Anatomymentioning
confidence: 99%